Hubungan Pengetahuan dan Sikap Ibu Terhadap Pijat Bayi di BPM Wulansari Kecamatan Binjai Timur Kotamadya Binjai tahun 2019 - Siskawati Amri (Jurnal Maternitas Kebidanan, 2020)
Baby massage is a relaxation technique given to babies that provides many benefits to children. This relaxation is given by using a gentle touch to the baby.This type of research used in this study is an observational analytic study with a cross sectional study approach to determine the relationship of knowledge and attitudes of mothers to baby massage in BPM Wulansari kecamatan Binjai Timur Kotamadya Binjai in 2019. The sample used in this study was a total sampling of 35 people. The results showed that there was a significant relationship between mother's knowledge of baby massage in BPM Wulansari kecamatan Binjai Timur Kotamadya Binjai Regency obtained by the calculation of the chi square statistical test that the value of p.value = 0.020 < 0.05 and there was a relationship between maternal attitudes towards baby massage in BPM Wulansari kecamatan Binjai Timur Kotamadya Binjai Regency obtained by statistical test calculations that the value of p.value = 0.032 < 0.05. It is expected that health workers will provide information on infant massage during counseling or other events such as posyandu so that the community can add insight into baby massage.